2008
DOI: 10.1128/aem.00366-08
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Accumulation of Cyanophycin in Transgenic Strains of Saccharomyces cerevisiae

Abstract: Cyanophycin [multi-L-arginyl-poly(L-aspartic acid) (CGP)] was, for the first time, produced in yeast. As yeasts are very important production organisms in biotechnology, it was determined if CGP can be produced in two different strains of Saccharomyces cerevisiae. The episomal vector systems pESC (with the galactoseinducible promoter GAL1) and pYEX-BX (with the copper ion-inducible promoter CUP1) were chosen to express the cyanophycin synthetase gene from the cyanobacterium Synechocystis sp. strain PCC 6308 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…In the past, bacteria were mainly applied for the synthesis of CGP (3,14,18,53), whereas recently there has been greater interest in synthesis in eukaryotes (26,42,50). CGP was accumulated to almost 7% (wt/wt) of dry matter in recombinant Nicotiana tabacum and Saccharomyces cerevisiae (26,50).In S. cerevisiae the arginine metabolism is well understood and has been investigated (30) (see Fig. 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, bacteria were mainly applied for the synthesis of CGP (3,14,18,53), whereas recently there has been greater interest in synthesis in eukaryotes (26,42,50). CGP was accumulated to almost 7% (wt/wt) of dry matter in recombinant Nicotiana tabacum and Saccharomyces cerevisiae (26,50).In S. cerevisiae the arginine metabolism is well understood and has been investigated (30) (see Fig. 2).…”
mentioning
confidence: 99%
“…Furthermore, two types of CGP were observed concerning its solubility behavior: (i) a water-insoluble type that becomes soluble at high or low pH (34, 48) and (ii) a water-soluble type that was only recently observed in recombinant organisms (19,26,42,50,56). In the past, bacteria were mainly applied for the synthesis of CGP (3,14,18,53), whereas recently there has been greater interest in synthesis in eukaryotes (26,42,50). CGP was accumulated to almost 7% (wt/wt) of dry matter in recombinant Nicotiana tabacum and Saccharomyces cerevisiae (26,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with yeasts maintained the idea of a water-soluble form and a modified composition of CGP synthesized by CphA 6308 . In 2008, Steinle et al (11) showed that in Saccharomyces cerevisiae expressing cphA 6308 , two forms of CGP are available. The major part accounts for a water-soluble form, and a minor part accounts for an insoluble form.…”
mentioning
confidence: 99%
“…Heterologously synthesized CGP, e.g., from bacterial hosts like Escherichia coli, Pseudomonas putida, and Ralstonia eutropha or from yeasts, is quite different (9,10,11). The water-insoluble cyanophycin-like material isolated from recombinant E. coli expressing cphA from Synechocystis sp.…”
mentioning
confidence: 99%